MyVivarium: A cloud-based lab animal colony management application with realtime ambient sensing - Robinson Vidva; Mir Abbas Raza; Jaswant Prabhakaran; Ayesha Sheikh; Alaina Sharp; Hayden Ott; Amelia Moore; Christopher Fleisher; Hailey Netherton; Evan Goldstein; Pothitos M. Pitychoutis; Tam V. Nguyen; et al. (Computational and Structural Biotechnology Journal)
Management of research-animal colonies is vital for lab productivity in preclinical research. Labs often rely on inefficient paper-based or spreadsheet-based methods to manage animal colonies. Dedicated software-based solutions are generally expensive and many lack remote access. Currently available open-source alternatives are difficult to implement and deploy. These solutions also do not have the capability to track ambient variables that affect colony well-being. We built MyVivarium, an open-source database management web application to address these gaps. MyVivarium can be easily deployed to the cloud and sustained for a cost comparable to starting and maintaining a lab website. Using MyVivarium, lab members can collaboratively track individual animals within a database. Physical identities of cages map onto the database using QR codes, enabling quick and easy record-keeping on mobile devices. Lab administrators can assign tasks to users with reminders for experiments or cage maintenance. Finally, we designed a low-cost system to sense ambient humidity, temperature, vivarium worker activity, and room illuminance. These data are then sent to MyVivarium in realtime providing information relevant to colony well-being. Taken together, MyVivarium is a novel, open-source, cloud-based application template that provides a low-cost, simple, and efficient way to digitally manage research-animal colonies.